2016
DOI: 10.1007/164_2016_116
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of Opioid Receptors in the GI Tract: Experimental Evidence and Therapeutic Relevance

Abstract: Opioid drugs are prescribed extensively for pain treatment but when used chronically they induce constipation that can progress to opioid-induced bowel dysfunction. Opioid drugs interact with three classes of opioid receptors: mu opioid receptors (MORs), delta opioid receptors (DOR), and kappa opioid receptors (KORs), but opioid drugs mostly target the MORs. Upon stimulation, opioid receptors couple to inhibitory Gi/Go proteins that activate or inhibit downstream effector proteins. MOR and DOR couple to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 82 publications
(138 reference statements)
1
101
0
4
Order By: Relevance
“…5 Previous reports have indicated that the activation of these three opioid receptors is all associated with the inhibition of the acetylcholine and purine/nitric oxide release from the enteric neurons, causing gastrointestinal (GI) inhibition. 6 The MOP (eg, morphine and DAMGO) and DOP (eg, DPDLE) receptor agonists were reported to inhibit GI transit dose-dependently. 7 KOP receptor is expressed primarily in the myenteric plexus.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous reports have indicated that the activation of these three opioid receptors is all associated with the inhibition of the acetylcholine and purine/nitric oxide release from the enteric neurons, causing gastrointestinal (GI) inhibition. 6 The MOP (eg, morphine and DAMGO) and DOP (eg, DPDLE) receptor agonists were reported to inhibit GI transit dose-dependently. 7 KOP receptor is expressed primarily in the myenteric plexus.…”
Section: Introductionmentioning
confidence: 99%
“…Lembo et al showed that the μ‐opioid agonist, fentanyl, inhibits the perception of phasic rectal distention in a dose‐dependent fashion. In addition, activation of μ and δ opioid receptors reduces active Cl − secretion and passive water movement into the colonic lumen by inhibiting submucosal secretomotor neurons, which can result in stool of more solid consistency …”
Section: Introductionmentioning
confidence: 99%
“…In addition, activation of μ and δ opioid receptors reduces active Cl − secretion and passive water movement into the colonic lumen by inhibiting submucosal secretomotor neurons, which can result in stool of more solid consistency. 11 Peripherally active μ-opioid receptor antagonists (PAMORA) have emerged as a treatment option for chronic opioid-induced constipation (OIC). 12 Naloxegol is a novel PAMORA which is efficacious in the treatment of chronic OIC when administered orally at a dose of 25 mg daily.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is supported by our findings that both TMEM16A inhibitor and loperamide delay gastric emptying, whereas only loperamide slowed whole-gut transit. Opioids have multiple actions on gut, including inhibition of ICCs by activating K + -ATP channels and suppression of enteric neurons and intestinal secretion, which indirectly inhibits stretch-induced motility (30). Because TMEM16A is not expressed in enterocytes or enteric neurons, TMEM16A inhibition is not expected to affect the determinants of gut motility other than ICC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were administered TM inh -23 at 10 mg/kg (in saline containing 5% DMSO and 10% Kolliphor HS 15) either intraperitoneally or by oral gavage. Blood samples were collected at 15,30,60,120, and 240 min by orbital puncture and centrifuged at 5000 rpm for 15 min at 25°C to separate serum. Solid-phase extraction columns (C18, HyperSep 60108-304; Thermo Fisher Scientific, Waltham, MA, USA) were conditioned with methanol (2 ml) followed by PBS (2 ml).…”
Section: Pharmacokineticsmentioning
confidence: 99%